2013
DOI: 10.1186/2050-2974-1-32
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptom trajectories in adolescence: effects of time, participant sex, and early adolescent depressive symptoms

Abstract: BackgroundAdolescence is a period of developmental risk for eating disorders and eating disorder symptoms. This study aimed to describe the prevalence and trajectory of five core eating disorder behaviours (binge eating, purging, fasting, following strict dietary rules, and hard exercise for weight control) and a continuous index of dietary restraint and eating, weight and shape concerns, in a cohort of male and female adolescents followed from 14 to 20 years. It also aimed to determine the effect of early ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 50 publications
(84 reference statements)
11
52
0
Order By: Relevance
“…The Raine Study eating disorder assessment items, and diagnostic algorithms for determining DSM‐5 eating disorders, are outlined in detail elsewhere . Briefly, eating disorder symptoms were assessed using 24 self‐report items adapted from the Eating Disorder Examination‐Questionnaire (EDE‐Q) .…”
Section: Methodsmentioning
confidence: 99%
“…The Raine Study eating disorder assessment items, and diagnostic algorithms for determining DSM‐5 eating disorders, are outlined in detail elsewhere . Briefly, eating disorder symptoms were assessed using 24 self‐report items adapted from the Eating Disorder Examination‐Questionnaire (EDE‐Q) .…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, many researchers have tried to explore different factors as possible triggers for binge eating (e.g. Allen, Crosby, Oddy, & Byrne, 2013;NeumarkSztainer et al, 2011). Studies on the dispositional characteristics have identified impulsivity trait as consistently associated with binge eating (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The debate over whether DE should be viewed as dimensional or categorical has raged for years, but both views seem desirable for representing the full spectrum of DE and detecting DE as early as possible [50]. Usually, DE has been studied by first examining a number of DE indicators, such as eating and/or shape concerns, and then relating either individual DE indicators or the total scores of those indicators to different psychosocial problems such as depression or self-esteem (e.g., [2, 40, 43]). A variable-oriented approach, built on the examination of linear relationships and mean differences, provides important knowledge about the relationships between various DE indicators and psychosocial difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…DE, regardless of the severity, is also correlated with depressive thoughts [9], while depressive symptoms at age 14 appear to increase eating disorder symptoms in Australian girls at age 20 [2]. Furthermore, depressive symptoms, other psychiatric disorders, and suicidality were all found to be associated with DE among American adolescents of both genders [43, 45], while negative affect is a good predictor of DE in young men [25].…”
Section: Introductionmentioning
confidence: 99%